Salmonella and the Media: A Comparative Analysis of Coverage of the 2008 Salmonella Outbreak in Jalapenos and the 2009 Salmonella Outbreak in Peanut Products - Kori Barr; Erica Irlbeck; Cindy Akers (Journal of Applied Communications, 2012)
The purpose of this study was to catalog and compare data from the coverage of two different Salmonella outbreak events in the United States through the lens of framing theory. Using qualitative content analysis, the transcripts of television newscasts that covered the 2008 Salmonella outbreak in tomatoes and jalapenos and the 2009 Salmonella outbreak in peanut products were researched and analyzed. These transcripts were taken from ABC, CBS, NBC, and CNN for both outbreaks. The researchers determined that while the manner in which the stories were framed was similar in some respects, such as story presentation and attitudes, there were also differences, particularly in regard to interview sources used. Tomato growers were used as sources in the 2008 outbreak, but peanut farmers were not used in the 2009 outbreak, where victims and politicians were favored. However, it was determined this had no overall effect on the accuracy, fairness, or overall economic or social impact of the stories presented.
Keywords: salmonella; media coverage; framing theory